Lack of Adjuvant Radiotherapy May Increase Risk of Retropharyngeal Node Recurrence in Patients with Squamous Cell Carcinoma of the Head and Neck after Transoral Robotic Surgery - Waleed F. Mourad; Dukagjin M. Blakaj; Rafi Kabarriti; Rebekah Young; Rania A. Shourbaji; Jonathan Glanzman; Shyamal Patel; Ravindra Yaparpalvi; Shalom Kalnicki; Madhur K. Garg (Case Reports in Oncological Medicine)
Purpose. Transoral robotic surgery (TORS) has increased in popularity in the management of squamous cell carcinoma of the head and neck. However, TORS does not address the neck or retropharyngeal nodes (RPN). In the current report, we highlight the impact of the lack of adjuvant radiotherapy on RPN recurrence after TORS. Materials and Methods. A 58-year-old Caucasian male presented with squamous cell carcinoma of the head and neck of unknown primary. He was offered radiotherapy as a definitive management for clinical stage T0N2aM0, stage IVA, but he opted to left neck dissection. Follow-up PET-CT scan revealed recurrence in the left base of tongue and right level II lymph node. He was offered radiotherapy which he declined and opted to TORS and right neck dissection. Follow-up PET-CT scan showed recurrence in left RPN for which he underwent salvage concurrent chemoradiotherapy to 70 Gy. Results. After a followup of 9 months from the date of salvage chemoradiotherapy completion, the patient is with no evidence of disease. Conclusions. TORS followed by adjuvant radiotherapy seems reasonable in the context of squamous cell carcinoma of the head and neck due to the odds of RPN involvement. Further reports are warranted to optimize post-TORS adjuvant treatment.